ChemInform Abstract: I2—PPh3 Mediated Spiroannulation of Unsaturated β‐Dicarbonyl Compounds. The First Synthesis of (.+‐.)‐Negundoin A. Issue 9 (4th March 2014) - Tapia, Ruben; Cano, M. Jose; Bouanou, Hanane; Alvarez, Esteban; Alvarez‐Manzaneda, Ramon; Chahboun, Rachid; Alvarez‐Manzaneda, Enrique
Abstract Unsaturated β‐dicarbonyl compounds, e.g. (I), (III)/(VI), (VIII), and (X) undergo intramolecular cyclization by reaction with a catalytic amount of I2—PPh3 affording spiro enol ether derivatives with complete regio‐ and stereoselectivity.